The Future of the NCVS: Findings From the Multiyear Effort to Design the New Instrument and Plans for Implementation - Truman, Jennifer L. (Journal of contemporary criminal justice, 2025)
During the past 50 years, various changes and improvements to the National Crime Victimization Survey (NCVS) have occurred. During this time, the NCVS has provided important national data on personal and household victimization and has remained a key resource for understanding victims’ experiences. As the survey continues to evolve over time to address emerging data needs, this article provides details on the most recent multiyear effort to redesign the NCVS instrument. This effort was focused on three main goals: modernize the organization and content of the NCVS instrument, increase the quality of information collected and efficiency of the instrument flow, and improve the measurement and classification of crime. As we look forward to the next 50 years of NCVS data collection, the new NCVS instrument will continue to be a rich data source for understanding criminal victimization and the resulting consequences.